Satirical political communication 2019 Indonesia’s presidential election on social media - Anang Sujoko (Informasi, 2020)
This study aims to reveal how satirical political communication by three kinds of social media accounts that have a large followers in Indonesia in the theme of the 2019 Presidential Election. Using Van Dijk’s critical discourse analysis model, this study uncovered the discourse that underlies criticism of candidates for presidential and vice-presidential candidates 2019 on Youtube, Facebook, and Twitter. The research found Prabowo vs. Jokowi’s rap battle by skinnyindonesia24, nurhadi_aldo’s Instagram account, and #2019GantiPresiden as the most prominent accounts that distributed satire political communication. The owner of a social media account produces messages based on a lively and controversial issue on social media. Account #2019GantiPresiden even tends to criticize incumbent candidates because they see that the mainstream media does not do its role. Nurhadi_aldo’s account manager sees sharp polarization between supporters of two pairs and tends to criticize controversial incumbent candidate programs. Skinnyindonesia24 reduces the polarization that is getting stronger by more balanced criticizing the competition of two presidential candidates through rap music. This study convinces that the nature of satirical political communication work efficiently because the content does not cross agreed-upon political boundaries and cultural spaces.Fokus penelitian ini ada pada komunikasi politik yang terjadi di platform media sosial selama pemilihan presiden 2019 di Indonesia. Menggunakan model analisis wacana kritis Van Dijk, penelitian ini mengungkap wacana yang mendasari kritik terhadap calon pasangan president dan wakil presiden 2019 di Facebook, Twitter, dan Youtube. Hasil penelitian menemukan pertarungan rap Prabowo vs Jokowi oleh skinnyindonesia24, akun Instagram nurhadi_aldo, dan #2019GantiPresiden sebagai akun paling menonjol yang mendistribusikan komunikasi politik sindiran. Sindiran dan humor dapat menjadi bentuk komunikasi politik bagi publik untuk mengritisi kandidat dengan aman. Pemilik akun media sosial memproduksi pesan berdasarkan isu yang ramai dan kontroversial di media sosial. Akun #2019GantiPresiden bahkan cenderung mengritisi kandidat petahana karena melihat tidak netralnya media mainstream dalam memberitakan para kandidat. Pengelola akun nurhadi_aldo melihat polarisasi yang tajam di antara pendukung dua pasangan dan cenderung mengritisi program-program kandidat petahana yang kontroversi. Uskinnyindonesia24 meredam polarisasi yang semakin kuat dengan lebih seimbang mengritisi persaingan dua kandidat calon presiden melalui musik rap. Studi ini menunjukkan bahwa sifat komunikasi politik satir memungkinkan untuk bekerja secara efisien karena konten dan kemasan ide tidak melewati batas politik yang disepakati dan ruang budaya.